How Status-seeking States Can Cooperate: Explaining India–China Rapprochement After the Doklam Standoff. (June 2019) - Xie, Chao
Noticing the gap in the existing literature, this article attempts to argue that status-seeking motives do not necessarily result in zero-sum games and hence tries to summarise conditions for status-seekers to manage conflicts and realise cooperation with one another through creative use of social mobility and creativity strategies. As a case study, this article examines the evolving relations between India and China since 2013 and demonstrates how relations between these two status-seeking states can become confrontational with conflicting status-seeking incentives. For some time, the status competition seemingly dominated their interactions, when India was not willing to accept China's power status second only to the USA, and China reluctant to recognise India as another rising power with nuclear capabilities. After the Donglang (Doklam) standoff, both governments are finding ways to manage an indirect path for cooperation through a newly discovered multilateral framework. The elements contributing to the stability of their relations lie in their choice of international identity and political calculations in which they can engage with the other based on their shared interests in fostering solidary among developing countries.